ASEAN (in)Security Community - Mohamad Rosyidin (Journal Of Global Strategic Studies, 2023)
The existence of arms modernization can be regarded as the high degree of security dilemma among states. In Southeast Asia, the fact that defense budget escalation followed by the military modernization may be the biggest obstacle to create an ASEAN Security Community. Unfortunately, there have been a little attention on the issue studying the correlation between arms modernization and the prospect of ASEAN Security Community. This paper seeks to fill the gap by analyzing how arms modernization in Southeast Asia is counterproductive to the ASEAN Security Community development. Using constructivism in International Relations, this paper argues that arms modernization among several ASEAN member states hinders collective identity building as a fundamental factor behind the security community. This argument implies that the formation of ASEAN Security Community will not create long-lasting peace in the region. This paper suggests that ASEAN should focus on collective identity formation to strengthen its own body institution rather than merely declare in a formal treaty.